Quest for Destiny in Paulo Coelho's The Alchemist (Pursuits: A Journal of English Studies, 2022)
In the novel, The Alchemist, Paulo Coelho explores how people attain their destiny. The novel revolves around the story of Santiago (the protagonist), a young Andalusian Shepherd. He dreams of buried treasure in Egypt while sleeping under a sycamore tree in an abandoned church in Spain. He undergoes difficulties and moves to Egypt to discover his destiny. In his journey, he gets assistance from disguised teachers. Ultimately, he finds his treasure not in Egypt, but in the abandoned church, back in Spain. The study has particularly used Jung's theory of shadow, anima, and personality as theoretical tools to analyze the narrative as it delves into the unconscious.